Produção científica do periódico Cadernos Brasileiros de Terapia Ocupacional no período de 2012 a 2017: um estudo bibliométrico - Santarpio, Éder José (2020)
Introduction: Scientific communication is an important stage in the production of knowledge, as it is through it that the process of knowledge transmission occurs. Among formal communications, scientific journals occupy a prominent place, as it is one of the main and most widespread means of scientific communication. Because it is one of the main means of scientific communication, the scientific journal becomes an object of extreme importance for bibliometric studies. Bibliometrically evaluating a given scientific journal allows to reveal, by obtaining indicators, certain characteristics that will serve as a basis for the representation of the scientific field linked to the journal. Objective: the study has as its general objective to map knowledge production in Occupational Therapy in the journal Brazilian Journal of Occupational Therapy, between the years 2012 to 2017, through the bibliometric approach. Methodology: Based on the objectives, the research can be classified as exploratory and descriptive with a quantitative and qualitative approach (multimethod). The research was developed in the following stages: 1) Construction of the theoretical framework - Scientific communication; the role of journals in the formal scientific communication process; bibliometry; Science, Technology and Society. 2) Elaboration of the collection protocol and the definition of the technological resources used in the study. 3) Data collection: Data were collected for 417 articles, 26 articles from dossiers and 25 editorials published in the journal Brazilian Journal of Occupational Therapy. 4) To store the data, Microsoft Office Excel® and Microsoft Office Word® spreadsheets were used. Vantage Point® software, scriptLattes and Microsoft Office Excel® were used to process the collected data. Results and Conclusions: It was found that the area has multidisciplinary characteristics, but most are linked to the large area of Health; the predominance of females in the area of Occupational Therapy was confirmed; a collaborative authorship process was identified; with regard to the authors' productivity, it was possible to verify that there is a low dispersion in relation to their productivity. It was possible to identify the internationalization of the journal and, as a consequence, the influence of foreign research on it; the results revealed that the majority of authors are linked to Public Institutions of Higher Education. We can conclude, based on the data of this research, the relevance of this journal for the area of Occupational Therapy in Brazil.